KONSEP STRATEGI BELAJAR MENGAJAR BAHASA ARAB - LUBIS, ALI ASRUN (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Learning Arabic language (Foreign language) is different with mother tongue or first language. That is why; the leraning strategy must be different in method, material and the strategy. Learning Arabic language has skills such listening, reading speaking and writing. It is harder because it must be related to mother tongue system to Arabic language. In leaning Arabic language is needed its leaning strategy. It provides: kinds of strategy and ability to choose and use them.